PENGARUH KETERLIBATAN PEMAKAI, PENDIDIKAN PEMAKAI SISTEM, KAPABILITAS PERSONAL SISTEM INFORMASI DAN DUKUNGAN MANAJEMEN PUNCAK TERHADAP EFEKTIVITAS PENGGUNAAN SISTEM INFORMASI AKUNTANSI - Ni Wayan Fina Kastania (UNHI Press, 2022)
The effectiveness of an accounting information system is a measure that shows the extent to which the target pool of resources is organized to collect, process, and store electronic data, then convert it into useful information and provide the required formal reports properly. This study aims to determine the effect of user involvement, user system education, information system personal capabilities, and top management support on the effectiveness of accounting information system users. This research was conducted at the Savings and Loans Cooperative in Ubud District. The sample in this study were 45 cooperative employees. The sampling method used is proposive sampling. The data analysis techniques used in this study are Descriptive Statistics, Validity Test, Reliability Test, Classical Assumption Test, Multiple Linear Regression, Coefficient of Determination, F Test, and t Test. From the results of this study, the user involvement variable has a positive and significant effect on the effectiveness of the use of accounting information systems. The system user education variable has a positive and significant effect on the effectiveness of the use of accounting information systems. The variable of personal capability of information systems has a positive and significant effect on the effectiveness of using accounting information systems. The top management support variable has a positive and significant effect on the effectiveness of the use of accounting information systems